Tax treatment of the donations for rural communities, native and indigenous development as a result of mining activities - Núñez Kcomt, Karen (2016)
In recent decades, with the growth and development of extractive activities, mainly in the mining sector, now become one of the pillars of the Peruvian economy, mining companies have been provided with a series of mechanisms and legal tools in an effort to maintain a mining operation within the framework of social responsibility and sustainability, adding to this, a latent need to find a formula to deal with the social conflicts that have become themselves the exercise of that activity in our country. So that legal figures that almost forgotten as the Grant, previous mining boom since the early 90’s has been progressively gaining prominence.In this sense, it is interesting to conduct an analysis of the contract of donation and its current policy, which we believe, will help to obtain a clear and concrete fiscal outlook in the mining investor positions, Peruvian state and peasant communities and native peoples indigenous; helping to channel acts of donation, in a formal manner